The right of the child to identity in the context of reproductive cell donor anonymity rules - Mladenović Tamara (Anali Pravnog Fakulteta u Beogradu)
The right of the child to identity has been gaining importance in the efforts to revise legislation on donor anonymity in a large number of European countries. However, certain national legislations are still in favor of the concept of the identity disclosure prohibition, while some envision a mixed model, with the aim of balancing conflicting interests. The debate is centered on the donor and parent's right to privacy and the child's right to know their biological origins. An analysis of solutions from various European states, as well as the positions of the authorities overseeing the implementation of the most important treaties, has led to the development of guidelines when weighing interests in a conflict. Although an ideal solution is difficult to imagine, a system that protects the interests of all parties, focusing on the protection of the child's rights, could be satisfactory.